The Industrialized Building System (IBS) as an alternative to the conventional construction method / Nurul Fatin Idayu Azman - Azman, Nurul Fatin Idayu (2021)
Malaysia construction sector currently face a significant demand in development. This influenced the rise of projects in the construction sector however causing several issues regarding quality and productivity of project and there is a rise of project abandoned due to financial issues. IBS is a construction evolution that uses new and creative techniques that is presently being used in Malaysia. However, the most of projects in Malaysia are completed using this approach only in metropolitan areas, and it has not been embraced by every state in Malaysia. Hence, this research aims to be focusing on the implementation of the IBS method as a solution for issues in Malaysian construction industry in order the ensure the project finish on time. It identifies the factors on why this method should by applied by construction parties. The questionnaires were distributed to collect the data and been analyzed using Google Form platform to find frequency of analysis and mean score. The results demonstrated the construction practitioner's perspective in the adaption of this system and the element of system implementation based on their experience. IBS initiatives must be adopted by both generations, not only the younger ones. By evaluating all these factors, the outcome may be used as a guideline to enhance the present building project's performance in the future.